The Cultural Role of Local Community-Based Organizations in Promoting the Work of National Civil Apparatus in Northern Lampung Province - Agung Ilmu Mangkunegara; Muh. Ilham Muh. Ilham; Murtir Jeddawi; Sampara Lukman (Yayasan Riset dan Pengembangan Intelektual, 2023)
The aim of this research is to analyze the role of Piil Pesenggiri culture in improving the performance of ASN in North Lampung Regency. Based on the empirical data above, it shows that the programs implemented relating to the performance and discipline of state civil servants in North Lampung Regency are not yet in line with the implementation of Regional Regulation No. 2 of 2008 concerning the Maintenance of Lampung Piil Pesenggiri Culture have not played a role in improving the performance of ASN in North Lampung Regency. The method used in this research is a qualitative method, which is intended to describe or provide an overview of phenomena that occur in the field. The results of the research show that the cultural role of the Piil Pesenggiri Organization is very good as a benchmark for ASN in North Lampung Regency in their work, because the Piil Pesenggiri culture has guided every action or behavior that must be carried out to maintain self-esteem, and must not be done to avoid embarrassment. The Piil Pesenggiri Organizational Culture can improve the performance of ASN in North Lampung Regency, this is based on results-oriented performance as guided by Sakai Sembayan values to provide benefits to others.